A Mexican soccer club, its resources and the relationship with an organized group of supporters in the context of 2015 to 2021: La Máquina de Cruz Azul - González, Sergio Fernández (2022)
This ethnographic work, is based on my own field research, provides a close look at the interior of a Mexican soccer team, Cruz Azul, and the relationship with the organized group of fans "La Sangre Azul". For this study I carried out a documentary research work, and also a social study in which I conducted two hundred interviews with members of the fan club, and lived with them in the stadium where I observed their relationship with the club management. On the other hand, I lived with the fans at the stadium and around their neighborhoods. The investigation demonstrates the organization of the supporters, its members, the relationship with the kinship unit, and the relationship with the soccer club. The work has several results, one of them was to understand the relationship with the club managements, the clientel relationship of the organized fans with the soccer club officials, and to understand, in this sense, the relationship of closeness and distancing of the fans with the direction of the Cruz Azul club.